Dissipative particle dynamics simulations of water droplet flows in a submicron parallel-plate channel for different temperature and surface-wetting conditions. (16th September 2016) - Yamada, Toru; Johansson, Erik O.; Sundén, Bengt; Yuan, Jinliang
ABSTRACT: The effects of temperature-dependent thermophysical properties on droplet flow characteristics in a parallel-plate channel at submicron scale are investigated. The dissipative particle dynamics method with many-body (MDPD) and energy conservation (DPDe) configurations (MDPDe) was used. Droplet flows were simulated to study the effects of the temperature difference between top and bottom walls, body force on MDPDe particles, and wall-wetting conditions. The effects on the droplet flow were discussed. Droplet flows with a subzero wall temperature were simulated. An ice layer was formed on the wall. Its thickness and shape changed depending on surface wetting, temperature gradient, and body force.